The Effectiveness of Corruption Eradication: Integrated System Approach - Timbonga, Yotham Th (2017)
The eradication of corruption must be done comprehensively. Therefore, the conventional legal approach has been inadequate in dealing a systematic and widespread modus operandi of corruption and extraordinary crimes. This research uses normative-research method. This research was conducted in Makassar as the Capital of South Sulawesi Province and Mamuju City as the Capital of West Sulawesi. The results shows that corruption eradication as an integrated manner has not been effectively maximized, because it is not supported by sufficient human resources, qualified and moral. To create an integrated anti-corruption eradication effectiveness, it is suggested repressive and preventive actions be undertaken simultaneously and integrated, supported by sufficient human resources, qualified and morally supported by adequate means and costs as well anti-corruption communities. In addition, to eradicate corruption as the embodiment of immoral behavior, it is suggested that moral education and anti-corruption embed shameless cultural values to corrupt as national programs and national movements to create the same motivation, perception and spirit in eradicate corruption. Keywords: Corruption, Criminal Law, Integrated Syste